Accountability of the Integrity Zone Program Towards a Corruption-Free Region at the Ministry of Religious Affairs Office in Baubau City - Asmiddin Asmiddin; La Didi; Emiryanti Emiryanti (INFOKUM, 2025)
The purpose of this study is to describe the accountability of the Integrity Zone Program towards a Corruption-Free Area (WBK) at the Baubau City Ministry of Religious Affairs Office using the approach (Halim, 16) including the implementation of the program, the suitability between targets and achievements, and the clarity of the program's goals and objectives. This research method uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Data sources were obtained from informants through direct observation and interviews and documents obtained in the form of regulations and processing. Data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data presentation, and drawing conclusions and verification. The results of the study indicate that program accountability has been reflected in various positive achievements. In the outcome dimension, the WBK program encourages increased ASN discipline, consistent implementation of SOPs, and the birth of digital service innovations such as LKH Online, PTSP Digital, and the Halal Meatball Cart (GBH) program. This indicates an increase in efficiency, effectiveness, and professionalism of services. In the dimension of suitability of targets and achievements, most program indicators have been achieved, especially in terms of increasing service speed and public satisfaction. However, obstacles such as employee resistance, limited technical training, and gaps in technology utilization still hamper the optimization of overall program accountability. Meanwhile, in terms of clarity of goals and objectives, the program has a specific policy direction outlined in official documents and supported by internal socialization. However, substantive understanding of integrity values is not yet fully shared among technical implementers.